Manajemen Layanan Asrama MAN 2 Jember (Studi Kasus: Peran Kepala Asrama Dalam Pengelolaan Layanan Asrama) - Rofiq Hidayat; Revina Dewi Agustin; Luluk Atul Fitriyah; Najibur Rahman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research uses qualitative research with a case study approach. The research was conducted at the Madrasah Aliyah Negeri 2 Jember Dormitory. The aim of this research is to analyze how the planning, organization, implementation and evaluation of dormitory service management by the dormitory head Mrs. Munadiroh, S.Pd. in managing the dormitory at Madrasah Aliyah Negeri 2 Jember. The results of the research showed that the head of the girls' dormitory at Madrasah Aliyah Negeri 2 Jember, Mrs. Munadiroh, S.Pd. able to carry out dormitory service management activities by supervising or monitoring to see whether dormitory programs, activities and implementation are running in accordance with the curriculum. In the process of planning, organizing, implementing and evaluating the dormitory, namely: 1) the dormitory head is able to carry out well starting from planning and implementing dormitory activities and programs, while planning involves all dormitory personnel; 2) Organizing by determining educational resources and other necessary resources including funds to fulfill the implementation of the dormitory and also facilities and infrastructure to support the learning process or dormitory development; 3) Able to mobilize his subordinates in accordance with Standard Operating Procedures or duties and responsibilities as well as regulations for student needs in accordance with the curriculum; 4) The dormitory head is able to evaluate the implementation of the dormitory program and the duties of each dormitory personnel, student deficiencies and other obstacles in meetings held once a month.